# 1.09x-4(3x-9)=1.12(x+5)-2

## Simple and best practice solution for 1.09x-4(3x-9)=1.12(x+5)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 1.09x-4(3x-9)=1.12(x+5)-2 equation:

1.09x-4(3x-9)=1.12(x+5)-2
We move all terms to the left:
1.09x-4(3x-9)-(1.12(x+5)-2)=0
We multiply parentheses
1.09x-12x-(1.12(x+5)-2)+36=0

We calculate terms in parentheses: -(1.12(x+5)-2), so:
1.12(x+5)-2
We multiply parentheses
1.12x+5.6-2
We add all the numbers together, and all the variables
1.12x+3.6
Back to the equation:
-(1.12x+3.6)

We add all the numbers together, and all the variables
-10.91x-(1.12x+3.6)+36=0
We get rid of parentheses
-10.91x-1.12x-3.6+36=0
We add all the numbers together, and all the variables
-12.03x+32.4=0
We move all terms containing x to the left, all other terms to the right
-12.03x=-32.4
x=-32.4/-12.03
x=2+1.9216589861751/2.7718894009217

`